Measuring learning from interventions through participatory processes - Shelton, Rebecca E.; Janssen, Marco A.; Meinzen-Dick, Ruth S. (Center for Behavior, Institutions and the Environment, Arizona State University, 2018)
There is an increasing use of models and games as interventions in participatory processes. Those interventions facilitate exploration and learning in a safe simulated environment. However, how do we measure if learning takes place, whether it results in behavioral change and whether it persists? We review the existing literature on social learning through participatory processes and how the impact of those interventions are measured. We identify a number of challenges and present a framework that aims to explicitly specify operational measurements into different levels of learning.